Model of manual car wash system / Mahyuddin Mahmud, Mohd Hairi Abd Hadi and Zulhilmi Abu Shahar - Mahmud, Mahyuddin; Abd Hadi, Mohd Hairi; Abu Shahar, Zulhilmi (2001)
This is a report about the design, fabrication and demonstration of a car wash system. To demonstrate the working principle of the system, a support frame, pipelines are attached together with nozzles. This model is useful in making the initial study to reduce the human discomfort associated with conventional car washing methods. We used the microstation programme to make drawings of the model, the assembly drawing and orthographic part drawings. The details of the fabrication and testing of the model are presented.